Shadows of Leadership: The Lived Experiences of Oppressed Followers of Toxic Leaders - Walker, Steven; Watkins, Daryl (Journal of Leadership, Accountability and Ethics, 2020)
Toxic leadership has been shown to have devastating effects on employee performance and also detrimental impacts on employee psychological and emotional health (Einarsen et al., 2010; Kelloway & Barling, 2010; Mackie, 2008; Tepper, 2007). This qualitative research study investigates the experiences of toxic leadership in organizations reported by 175 followers. Follower experiences were analyzed through NVivo. Various themes of toxic leadership emerged, and a model of toxic leadership was created. This paper will discuss the findings of this study.